2011
DOI: 10.1093/nar/gkq1297
|View full text |Cite
|
Sign up to set email alerts
|

A BEAF dependent chromatin domain boundary separates myoglianin and eyeless genes of Drosophila melanogaster

Abstract: Precise transcriptional control is dependent on specific interactions of a number of regulatory elements such as promoters, enhancers and silencers. Several studies indicate that the genome in higher eukaryotes is divided into chromatin domains with functional autonomy. Chromatin domain boundaries are a class of regulatory elements that restrict enhancers to interact with appropriate promoters and prevent misregulation of genes. While several boundary elements have been identified, a rational approach to searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 70 publications
3
33
0
2
Order By: Relevance
“…It is possible that these sites represent non-functional BEAF sites, because BEAF is believed to be absent from all the species other than Drosophilids (30). Moreover, none of these boundaries contains palindromic BEAF sites as frequently seen in BEAF-dependent boundaries in Drosophila (66). Taken together, this study shows that mosquito boundary elements identified here employ GAF and CP190 for their enhancer-blocking activity.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that these sites represent non-functional BEAF sites, because BEAF is believed to be absent from all the species other than Drosophilids (30). Moreover, none of these boundaries contains palindromic BEAF sites as frequently seen in BEAF-dependent boundaries in Drosophila (66). Taken together, this study shows that mosquito boundary elements identified here employ GAF and CP190 for their enhancer-blocking activity.…”
Section: Discussionmentioning
confidence: 99%
“…Inverse PCR was performed following the published protocol 41 to determine the precise insertion site for useful lines. Embryos (0-12 h) were collected and stained for b-galactosidase (lacZ) activity according to the protocol 42 with minor changes 43 as outlined. Briefly, 0-to 12-h-old embryos were dechorionated in 50% bleach (sodium hypochlorite), washed and fixed in heptane saturated with 25% glutaraldehyde for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…5A). For example, the intergenic region between the genes myoglianin and eyeless contains a functional BEAF-32 binding site in D. melanogaster (Sultana et al 2011), but not in D. virilis. The distance between the two TSS's increased 10 times in D. virilis, and this change correlates with the loss of the BEAF-32 binding site in this species or the gain in D. melanogaster (Fig.…”
Section: Beaf-32 Insulator and Speciationmentioning
confidence: 99%